Estrategias didácticas y su incidencia en la lectura comprensiva de los niños del quinto año de básica de la escuela fiscal mixta “4 de mayo” del cantón Babahoyo - Otacoma Shangallimbay, Luis Fernando (2017)
Nowadays you can not educate for the present, nor for the immediate environment surrounding educational institutions, today you must train students, who are citizens, very soon professionals, who will need to have developed a profile required by the professional and professional world. Today's teachers can not ignore what happens in their environment, they must educate for the present, but also for the future, they must educate for the region, but also for the world and for this they need to know and become familiar with the standards international in each of the required competences. As you can see in the previous figure for both authors, strategic learning is the result of the interaction between the previous knowledge of a subject and the knowledge to be acquired, having the need, interest, desire and disposition, on the part of this subject, of there is no construction between the new knowledge and the bases that the individual has, you can not talk about strategic learning. Strategic learning is understood as the incorporation of new information into the cognitive structure of the individual, this will create an assimilation between the knowledge that the individual has in his cognitive structure with new information, facilitating learning, knowledge, a mental structure, with leads to a process which will be seen later. The methodology of working with classroom projects and group work is adequate to exploit the active participation of the student which allows him to create, approach and relate to contexts of joint work, opens the classroom to other educational spaces, incorporates the interests of the student, facilitates the autonomous search for additional information, decreases the directive role and the single source of the teacher's knowledge.